Analysis of maternal factors of the perinatal pathologies among women with menstrual cycle disorder - Malanchuk Олександра (Actual Problems of Medicine and Pharmacy, 2021)
The analysis of the course, completion of pregnancy in women with reproductive losses and menstrual irregularities, the formation of risk groups with the aim of improving the prevention system, early diagnosis of perinatal pathology and predicting healthy offspring was carried out.